Data Analysis and Validation of Acquired Temperature Data on Underwater Platform - Kumar, Arun; Anjaneyulu, Lokam (Defence Science Journal, 2018)
Underwater missiles are launched from canister by hot gasses produced by a gas generator. Hot gasses eject the missile out of canister, positioned on an underwater platform in high seas at a depth of 50 m to 70 m. During development phase of submarine launched missile, maximum number of physical parameters related to platform and launching mechanism are acquired on a data acquisition system on-board platform and selected critical parameters are transmitted to control station in real time through an optical data communication link. Missile parameters are recorded on-board and transmitted to the control station by delayed transmission technique once the missile is out of water. Exit velocity of missile is very important parameter for the missile trajectory and range, which depends upon the heat loss in canister and annular gap pressure between missile and canister during the ejection process. Prediction of exit velocity is validated by heat loss calculation by measured temperature at different stations during the test. Temperature measurement is carried out by sensors mounted on the inner wall of canister and also by jumping type of temperature sensor, which measures canister gas temperature. In spite of all efforts, few sensors do not work as expected. It is important to measure various parameters according to instrumentation measurement plan. In case of temperature measurement, sometimes, it is required to predict temperature at location, where sensor was originally not mounted. To validate the recorded test data, another set of data is needed for which one has to wait till next test is conducted that may take years and practically impossible to ensure identical test setup and environmental condition. A mathematical approach to predict temperature at required location and to validate the recorded test data is presented.